Facile fabrication of antioxidative and antibacterial hydrogel films to accelerate infected diabetic wound healing - Haodong Zhang; Qian Liang; Yanxiu Ji; Qi Chen; Weinan Jiang; Donghui Zhang; Yueming Wu; Liangmin Yu; Wei Chen; Runhui Liu (Bioactive Materials, 2025)
Diabetic wounds are accompanied with hemorrhage, excessive reactive oxygen species accumulation, microbial infection, and poor exudate management. Current dressings are insufficient to modulate the complex pathophysiological microenvironment of infected diabetic wounds. Here, we develop a facile-fabricated hydrogel film with potent antibacterial and antioxidative properties to significantly accelerate infected diabetic wounds healing. The hydrogel film demonstrates potent antibacterial efficacy against methicillin-resistant Staphylococcus aureus and Escherichia coli, efficient scavenging of the extra- and intracellular reactive oxygen species, and enhanced fibroblast migration. In the methicillin-resistant Staphylococcus aureus infected diabetic wounds model, the hydrogel film treatment leads to reduced methicillin-resistant Staphylococcus aureus load, eliminated exudate accumulation, and significantly accelerated wound healing. In addition, the hydrogel film achieves rapid hemostasis by effective wound adhesion and fluid absorption. Collectively, this study provides a promising therapeutic option to promote infected diabetic wounds healing and management.